Does background colouration affect the behaviour of tadpoles? An experimental approach with an odonate predator - Nomura, F.; De Marco, P.; Carvalho, A. F A [UNESP]; Rossa-Feres, D. C. [UNESP] (Taylor & Francis, 2013)
Predation is a primary driver of tadpole assemblages, and the activity rate is a good predictor of the tadpoles' tolerance for predation risk. The conflicting demands between activity and exposure to predation can generate suboptimal behaviours. Because morphological components, such as body colouration, may affect the activity of tadpoles, we predict that environmental features that enhance or match the tadpole colouration should affect their survival or activity rate in the presence of a predator. We tested this prediction experimentally by assessing the mortality rate of tadpoles of Rhinella schneideri and Eupemphix nattereri and the active time on two artificial background types: one bright-coloured and one black-coloured. We found no difference in tadpole mortality due to the background type. However, R. schneideri tadpoles were more active than E. nattereri tadpoles, and the activity of R. schneideri was reduced less in the presence of the predator than that of E. nattereri. Although the background colouration did not affect the tadpole mortality rate, it was a stimulus that elicited behavioural responses in the tadpoles, leading them to adjust their activity rate to the type of background colour. © 2013 Dipartimento di Biologia, Università degli Studi di Firenze, Italia.
Keywords: Eupemphix nattereri; habitat heterogeneity; Pantala flavescens; pattern of activity; predation; Rhinella schneideri; activity pattern; background level; behavioral ecology; behavioral response; color; dragonfly; experimental study; frog; hypothesis testing; larva; morphology; mortality; predation risk; predator; survival; toad; tolerance